To solve the system of equations using elimination, you want to multiply one or both equations by a constant to get the coefficients of either x or y to be the same or opposite. In this case, the y coefficients are 1 and -2, so we can multiply the first equation by 2 and the second equation by 1 to make the y coefficients the same.
The best way to begin would be to multiply both sides of the first equation by 2:
2(2x + y) = 2(-3)
4x + 2y = -6
Now, we have the two equations as:
4x + 2y = -6
3x - 2y = 2
By multiplying the first equation by 2, we made the y coefficients the same, which allows us to eliminate y when we add the two equations together.
Julie is asked to solve the system below by elimination. Which of the following steps would be the best way to begin?
I. 2x+y=-3 II. 3x-2y=2
1 answer